Spectrophotometric Determination of Phenolic Antioxidants - BALA SEKARAN, C.; VIJAYASARADHI, S.; PRAVEEN KUMAR, B.; SRILAKSHMI, CH. (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method for the determination of gallic acid was developed. This method is based on oxidative coupling reaction between gallic acid with phenol in the presence of hydrogen peroxide and enzyme horseradish peroxidase to produce coloured product, which is measured spectrophotometrically at 420 nm. The colour was stable for 70 min. Beer's law was valid within a concentration range of 25-250 μg/25 mL. All the variables were studied to optimize the reaction conditions. No interference was observed in the presence of common excipeints. The validity of the method was tested by analyzing gallic acid in oils. This method is successfully employed for the determination of gallic acid present in oils.